Counselling App on Android for UTHM Students with AES - Lee Kuan Yi; Mohd Foozy, Cik Feresa (Applied Information Technology And Computer Science, 2022)
The counselling app on Android for Universiti Tun Hussein Onn Malaysia (UTHM) students with Advanced Encryption Standard (AES) is designed to provide the counselling service to the students who are facing depression and anxieties. The students can send messages to the university counsellor if they are feeling low and unmotivated. The university counsellor can then reply to the student by giving some advice and motivation. All messages will be encrypted before they are stored in the database. The encryption algorithm used is the Advanced Encryption Standard with 256-bit of key size (AES-256). There are six modules in this application which include Login, Admin, Forgot Password, Message, Bulletin Board and DASS Test. The methodology used for the development of this project is the object-oriented software development model. The testing is done by 10 students and 4 counsellors in UTHM. The app has passed the functional testing and security testing.